Constructivism and the Quest for Cross Cultural Understanding - Folorunso, Paul Olorunsola (NIU Journal of Social Sciences; Vol 3 No 2 (2017): KIU Journal of Social Sciences, Vol. 3 No. 2, September 2017, 2017)
Culture is a human legacy bequeathed through human interactions with nature and the universe which he lives. It entails human capacity to express and act within specific environmental contingencies. Culture is the totality of man represented in the phenomena of knowledge, arts, morals, law, and custom as acquired by man in his society. However, culture is diverse and relative to people at specific periods, this diversity has generated spates of reaction among scholars. Our intention in this work is really not to examine the tension created as a result of human cultural diversity but to argue that a constructivist view of culture is key towards achieving cultural harmony that seeks understanding in uniqueness and differences for a better world. Constructivism is the hallmark of open-mindedness which enables us to recognize our differences and still able to absorb consciously from others. Keywords: culture, cross-cultural, understanding, constructivist, relative and diverse.